Fiber-reinforced liquid crystalline elastomer composite actuators with multi-stimulus response properties and multi-directional morphing capabilities. (1st May 2023) - Xia, Yuliang; Mu, Tong; He, Yang; Liu, Yanju; Leng, Jinsong
Abstract: Liquid crystalline elastomers (LCEs) are promising materials for soft actuations. LCE composites (LCECs), via the inclusion of fillers into LCEs, bring diverse functionalities and stimuli-responsive capabilities. It is still a challenge to improve the mechanical properties of LCEC and ensure that the material can perform reversible transformations. Here we present a cost-effective LCEC design and fabrication method by dispersing continuous carbon fibers and carbon nanotubes into LCEs, forming a new type of LCEC actuator. We found that through adjusting the angle (such as 45° and 90°) between the carbon fiber and the stretching axis of LCEC matrix, complex deformable geometries can be easily achieved including bending and twisting structures with enhanced storage modulus (400.9 MPa at 25 °C). Furthermore, the LCEC actuators could be driven by various stimuli including heat (120 °C), light (800 mW cm −2 ), and electricity (2.0 V). As a result, our new LCEC actuator outperforms other LCE actuators by having the largest number of morphing geometries and stimulus-responsive modes. Our LCEC design and manufacturing strategy represents a promising general methodology that can be easily extended to other continuous fibers (such as glass fiber, aramid fiber, etc.) filled LCECs, bringing even rich shape-changing capabilities that are needed for soft robots and beyond. Graphical abstract: LCEC actuators incorporated with continuous carbon fiber and carbon nanotube have been designed. The continuous carbon fiber can both adjust the deformation geometry and provide conductive path. Consequently, these actuators can be triggered by multi-stimulus method including heat, light, and electricity. Image 1